On the local time density of the reflecting Brownian bridge. (2000) - Gittenberger, Bernhard; Louchard, Guy
Abstract : Expressions for the multi-dimensional densities of Brownian bridge local time are derived by two different methods: A direct method based on Kac's formula for Brownian functionals and an indirect one based on a limit theorem for strata of random mappings.